Composition and structure of the cloud forest on Mt. Delaco, Gau, Fiji - Keppel, Gunnar; Thomas, N. (CSIRO Publishing, 2009)
The composition and structure of cloud forest on Mt. Delaco (715m), Gau, Fiji Islands, is investigated using a transect following a ridge. Diameter (dbh), height, epiphyte cover and distance to the nearest neighbour were measured for each plant of 5 or more cm in dbh. A total of 42 vascular species were identified. The canopy was 3-5m tall, with Alpinia boia reaching 7m in height. The tree fern Dicksonia brackenridgei dominated the vegetation, accounting for 56% of the total basal area. Rapanea myricifolia, Hedycarya dorstenoides and Ascarina diffusa were other common species. Epiphytes were abundant and epiphyte cover for most trees was more than 50%. The most common epiphytes were Nephrolepis tuberosa and Nephrolepis saligna, Collospermum montanum, Peperomia spp., mosses and filmy ferns (Hymenophyllaceae) were other common species. A species of Freycinetia was the dominant climber. There was a moderately strong correlation between epiphyte richness and dbh of the host species (r = 0.59). The limited literature on cloud forest in the tropical insular Pacific suggests that while many taxa are shared, the species composition may vary considerably on different mountains.